La estimulación temprana y su importancia en el desarrollo de habilidades sociales en los infantes de 1 a 2 años - Valverde Alvites De Arenas, Jackelyne Lizbeth (2018)
Early Stimulation considers a number of actions that improve the development of the child´s first years of life, even provides a wide range of activities that affect the construction of social skill that are manifested in the behavior. When consider early stimulation as thesis topic and the importance in the development of social skills in infants from1 to 2 years old, we intend to know the theories involved in this area, although we know very little about it in the area in wich we operate. When we consulted professionals, all the ideas and answers that we obtained were diffuse and without a concrete theory or scientific explanation. Therefore, the development of social skills in children from their first experiences through specific and concrete activities is of vital importance, and early stimulation is considered as a safe mean to enhance the development of these activities. The problem or our area is to ignore the appopriate strategies for early stimulation, because we know very little about it and this comes to us very synthesized through magazines or TV programs and instead of satisfying the doubts of the community that wants to apply them, generates more doubts. The present study tries to demostrate that if we provide out children with an early quality stimulation we will obtain an optimal development of their social skills guaranteeing their integral development, being they the direct beneficiaries.